The middle classes: An historic actor in today's global world. Issue 2 (10th September 2013) - Sassen, Saskia
Abstract : Saskia Sassen draws lines of shared experience between the protests of the 'modest middle classes' in diverse countries around the world, focusing on a common sense that the modern state is failing its people and a new conception of 'the street' as a space for political action and history‐making.